Oropharyngeal gonorrhoea infections among heterosexual women and heterosexual men with urogenital gonorrhoea attending a sexual health clinic in Melbourne, Australia. (December 2021) - Allen, Connor; Fairley, Christopher K.; Chen, Marcus Y.; Maddaford, Kate; Ong, Jason J.; Williamson, Deborah A.; Chow, Eric P.F.
Abstract: Objectives: There is limited evidence about the transmission and prevalence of oropharyngeal gonorrhoea in heterosexuals. From August 2017, Melbourne Sexual Health Centre (MSHC) began testing for oropharyngeal gonorrhoea among heterosexuals with untreated urogenital gonorrhoea. This study aims to determine the positivity of oropharyngeal gonorrhoea among heterosexuals diagnosed with urogenital gonorrhoea at MSHC between August 2017 and May 2020. Methods: We included individuals who had oropharyngeal gonorrhoea testing within 30 days of initial testing. We reported the number and proportion of oropharyngeal gonorrhoea positivity, stratified by gender and contact of gonorrhoea. The χ 2 test was performed to compare the oropharyngeal gonorrhoea positivity between groups. Results: Of 617 individuals with untreated urogenital gonorrhoea, 424 (68.7%) were tested for oropharyngeal gonorrhoea. Oropharyngeal gonorrhoea positivity was 38.9% (95%CI 34.2–43.7%, 165/424), and was higher in women than in men (115/252, 45.6% versus 50/172, 29.1%, p = 0.001). Furthermore, oropharyngeal gonorrhoea positivity was higher among individuals who were contacts of gonorrhoea cases compared to those who were not (29/44, 65.9% versus 136/380, 35.8%, p < 0.001). There was also no significant difference between women who were sex workers and those who were not (30/78, 38.5% versus 85/174, 48.9%, p = 0.126). Conclusions: Our data suggest that oropharyngeal gonorrhoea infection is common among heterosexual women and heterosexual men with untreated urogenital gonorrhoea. Testing heterosexual women and heterosexual men for oropharyngeal gonorrhoea will identify a significant proportion with unrecognized oropharyngeal infections whose recommended treatment is different in some countries.